2013
DOI: 10.1016/j.crci.2012.11.007
|View full text |Cite
|
Sign up to set email alerts
|

One-pot synthesis of 4,5-disubstituted 1,2,3-(NH)-triazoles by silica supported-zinc bromide in the aerobic condition

Abstract: An efficient one-pot cross-coupling/1,3-dipolar cycloaddition sequence was developed for a convenient synthesis of 4,5-disubstituted-1,2,3-(NH)-triazoles, starting from various acid chlorides, terminal alkynes and sodium azide in the presence of silica supported-zinc bromide under aerobic conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The reaction was carried out under anhydrous conditions at room temperature followed by the addition of sodium azide in CH 3 CN/H 2 O (3:1) by heating at 50 C for another 3 h to give 4,5-disubstituted 1,2,3-(NH)-triazoles. The synthesis of substituted triazole derivatives without using palladium or copper metal is one of the significant features of this synthetic method (Scheme 8) [24].…”
Section: Silica-supported Inorganic Salt Catalystsmentioning
confidence: 99%
“…The reaction was carried out under anhydrous conditions at room temperature followed by the addition of sodium azide in CH 3 CN/H 2 O (3:1) by heating at 50 C for another 3 h to give 4,5-disubstituted 1,2,3-(NH)-triazoles. The synthesis of substituted triazole derivatives without using palladium or copper metal is one of the significant features of this synthetic method (Scheme 8) [24].…”
Section: Silica-supported Inorganic Salt Catalystsmentioning
confidence: 99%
“…Another multicomponent approach (Figure 26 ) included consecutive reaction of terminal alkyne 183 with acyl halide 311 , and then with sodium azide with application of zinc bromide, which served as a catalyst for both steps of the process (Keivanloo et al, 2013 ).…”
Section: Main Partmentioning
confidence: 99%
“…Keivanloo et al exploited SiO 2 /ZnBr 2 for the synthesis of ynones 31 by cross-coupling of acid chloride with terminal alkynes and synthesis of 4,5-disubstituted 1,2,3-(NH)-triazoles. 32 Moreover, Kodomari and co-workers 33 also reported the synthesis of triarylmethanes and 9,10-diarylanthracenes and Clark et al 34 reported bromination of aromatic substrate using SiO 2 /ZnBr 2 catalyst. The catalyst possesses inherent environmentally benevolent properties such as non-toxicity, biocompatibility, physiological inertness, recyclability, inexpensiveness and thermal stability.…”
Section: Introductionmentioning
confidence: 99%